Bendamustine in combination with rituximab for elderly patients with previously untreated B-cell chronic lymphocytic leukemia: A retrospective analysis of real-life practice in Italian hematology departments. Issue 10 (October 2015) - Laurenti, Luca; Innocenti, Idanna; Autore, Francesco; Vannata, Barbara; Efremov, Dimitar G.; Ciolli, Stefania; Del Poeta, Giovanni; Mauro, Francesca Romana; Cortelezzi, Agostino; Borza, Paola Anticoli; Ghio, Francesco; Mondello, Patrizia; et al.
Highlights BR front-line therapy provides in elderly CLL patients a high response rate. More than 50% elderly CLL patients reduced bendamustine dose. del17 was the only unfavorable parameter for response rate and PFS.